A retrospective study of autologous stem cell mobilization by G-CSF in combination with chemotherapy in patients with multiple myeloma and lymphoma - Zheng, Gaofeng (Oncol Lett, 2020)
Factors affecting peripheral blood hematopoietic stem cell (PBSC) mobilization and collection were investigated in patients with multiple myeloma (MM) and lymphoma who were undergoing chemotherapy. Clinical data from 128 patients, including 53 MM and 75 malignant lymphoma (7 Hodgkin's lymphoma and 68 non-Hodgkin's lymphoma) cases were retrospectively analyzed. Autologous PBSCs were mobilized using granulocyte-colony stimulating factor (G-CSF) during chemotherapy, and collected using a continuous flow cell separation instrument. The yields of CD34+ cells per kilogram of patient body weight <2.0×10(6)/kg, >2.0×10(6)/kg or >5.0×10(6)/kg were defined as a failure, a success or ideal mobilization, respectively. In MM and lymphoma patients, the success rates of CD34+ cell acquisition were 73.6 (39/53) and 58.7% (44/75), the ideal rates were 43.4 (23/53) and 30.7% (23/75), and the failure rates were 26.4 (14/53) and 41.3% (31/75), respectively. Univariate and multivariate statistical analysis revealed that negative factors for PBSC mobilization in patients with MM were lenalidomide treatment, multiple chemotherapies, incomplete disease remission and low-level blood hemoglobin; in patients with lymphoma, the negative factors were the histological disease type, incomplete disease remission, being beyond the first-line of previous chemotherapy, multiple chemotherapies, chemotherapy with the HyperCVAD-B mobilization scheme, high-dose MTX/Ara-c (methotrexate/cytarabine) treatment, prolonged administration of G-CSF and low-hematocrit levels. In the present study, different factors influencing PBSC mobilization and collection in MM and lymphoma cases were identified. PBSC mobilization yielded sufficient CD34+ cell counts both in MM and lymphoma patients; however, the failure rates were relatively high.